The emotional perception and cognitive processing during multimedia learning in students with depressive tendencies - Wang, Ziyi; Wang, Junfei; Liu, Chengwei; Liu, Huiying; Cui, Lei (Frontiers in Psychology, 2025)
The impact of emotional design of pedagogical agent on learners' emotional perception and cognitive processing is the research focus in multimedia learning studies. While pedagogical agent's positive emotion facilitates learning among healthy students, how the pedagogical agent's emotion influences the emotional perception and cognitive processing in students with depressive tendencies remains unclear. This study investigated this issue by presenting emotional cues through both visual (facial expression) and auditory (voice tone) channels to students with depressive tendencies. Results found that learners perceived the negative emotion but not the positive emotion conveyed by the pedagogical agent's facial expression, supporting Beck's cognitive theory of depression. Compared to negative voice tone, positive voice tone enhanced the social connection between learners and the pedagogical agent, aligning with the positivity principle and emotional contagion theory. In addition, when the pedagogical agent's emotions across visual and auditory channels was congruent (both positive or negative), learners exhibited increased germane cognitive load and improved performance on transfer tests, supporting the congruency effect. Therefore, for learners with depressive tendencies, multimedia designers should prioritize auditory emotional cue and utilize the emotional congruency effect across channels to facilitate learner's emotional perception and cognitive processing.